The industrial internet of things and technological innovation in its applications for resources optimisation. (2017) - Neto, Albino Ribeiro; Ribeiro, Maira Fernanda Gizotti; Cunha, Gerson Gomes; Landau, Luiz
This paper presents a study on the use of industrial internet of things (IIoT), the use of IIot in the current Brazilian industry context, its basic differences from internet of things (IoT) and its expansion possibilities pointing out some challenges related to a new approach within the industry. The complex interconnection which is made possible through the IIoT is able to optimise resources and reduce exponentially the costs of production processes in most stages and is gradually changing the direction of society in labour relations. These advances in manufacturing processes are feasible as the internet of things is not simply inserting intelligence in equipment, but allowing interconnection, reconfiguring functions and anticipating loss of productivity or failures that might occur in real-time. Within this context, the IIoT can be understood as a broad and complex concept that encompasses asset and performance management areas, availability of increased data and intelligent corporate.